149 Service use related to violence against women and children during COVID-19. (20th November 2022) - Butler, Nadia; Quigg, Zara; Pearson, Isabelle; Yelgezekova, Zhamin; Nihlén, Aasa; Bellis, Mark A; Yon, Yongjie; Passmore, Jonathon; Aguirre, Isabel Yordi; Stöckl, Heidi
Abstract : Background: Globally, concerns have been raised that the priority implementation of public health measures in response to COVID-19 may have unintended negative impacts on a variety of other health and wellbeing factors, including violence. Aim: This study examined the impact of COVID-19 response measures on changes in violence against women and children (VAWC) service utilisation across European countries. Methods: A rapid assessment design was used to compile quantitative data related to changes in VAWC service utilisation during COVID-19. This included a survey distributed across WHO Europe Healthy Cities Networks and Violence Injury Prevention Focal Points, and a scoping review of media reports, journal articles, and reports. Results: Overall, findings suggested that there was a median reported increase in VAWC service utilisation of approximately 20% during the COVID-19 pandemic. Crucially, however, change in service utilisation differed across sectors with the highest median increase in utilisation for NGOs (48%), a relatively small median increase for law enforcement services (6%), and a small decrease for health and social services (-8%). Conclusions: The variation across sectors in changes in VAWC service utilisation has important implications for policymakers in the event of ongoing and future restrictions related to COVID-19 and more generally during other times of prolonged presence in the home. The increased global attention on VAWC during the pandemic should be used to drive forward the agenda on prevention, increase access to services, and implement better data collection mechanisms, to ensure the momentum and increased focus on VAWC during the pandemic is not wasted.